Forming and Maintaining Interpersonal Relationships - Lopes, M. J. (2019)
This chapter focuses on interpersonal, therapeutic relationships, what they are and how to form and maintain them. For many psychiatric/mental health (P/MH) nurses, such relationships are the core of P/MH nursing practice; for others, one cannot serve effectively as a P/MH nurse without operating within the context of interpersonal relationships. The chapter begins by identifying and discussing assumptions regarding nurse-patient relationships; following this, it focuses on the process(es) involved in forming and maintaining such relationships. The structure and phases of such relationships are then described and explored. The chapter then examines the nature and importance of evaluation in the context of therapeutic relationships. The chapter concludes by reasserting that forming and maintaining interpersonal relationships in P/MH nursing is a crucial therapeutic intervention and is, also, a fundamental nursing competency. Finally, the chapter makes the case for promoting an alliance between academic and clinical nurses to increase the research about interpersonal relationships and, in so doing, demonstrates the contributions of the interpersonal relationship to the health gains of client.